Introduction - Shehu, Fatmir Mehdi (International Institute for Muslim Unity (IIMU), 2024)
This edited book, entitled AbdulHamid AbuSulayman’s Contributions to Intellectual and Educational Reform, brings to light the ideas, thoughts, experiences, and contributions of AbdulHamid AbuSulayman to intellectual and educational reform presented in the scholarly writings and personal narratives of different scholars who contributed to this work. This book is the outcome of a research grant sponsored by the International Institute of Islamic Thought (IIIT), which started with the sponsorship of the International Conference on the Contributions of AbdulHamid AbuSulayman to Intellectual and Educational Reform and culminated into this volume. This introduction presents an overview of the subject discussed in this edited book and its content.